Changing Teachers' Epistemic Cognition: A New Conceptual Framework for Epistemic Reflexivity. Issue 4 (2nd October 2017) - Lunn Brownlee, Jo; Ferguson, Leila E.; Ryan, Mary
Abstract : There is increasing evidence to show that teachers' epistemic cognition is related to how they conceive of and engage in teaching; therefore it is important that teachers develop adaptive epistemic cognition. This article provides an overview of the different ways of theorizing and investigating changes in epistemic cognition for teaching and learning. A growing body of research shows that explicit reflection on epistemic cognition may be a useful way to promote change. Drawing on the work of Lunn Brownlee and Schraw and the Advanced Study Colloquium group described in the introduction to this special issue, we extend the concept of explicit reflection to encompass reflexive thinking. Reflexivity involves critical thinking that evaluates multiple perspectives in context and leads to specific action in the classroom. The 3R-EC Framework ( R eflection, R eflexivity and R esolved Action for E pistemic C ognition) for theorizing change in epistemic cognition is described and exemplified in the contexts of classroom practice and teachers' professional learning.